2004
DOI: 10.1093/carcin/bgh178
|View full text |Cite
|
Sign up to set email alerts
|

Soy processing influences growth of estrogen-dependent breast cancer tumors

Abstract: Soy-based products consumed in Asian countries are minimally processed whereas in the USA many of the soy foods and soy ingredients are highly processed. Soy foods contain complex mixtures of bioactive compounds, which may interact with one another. The objective of this study was to evaluate the ability of various soy products containing genistin, the glycoside form of genistein, to affect growth of MCF-7 cells transplanted into ovariectomized athymic mice. Products investigated included soy flour, two crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
127
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 42 publications
1
127
1
1
Order By: Relevance
“…However, unlike FS diet, the long-term administration of SP diet stimulated the growth of orthotopic MCF-7 xenografts in ovariectomized mice, which concur with the previous studies of Allred and co-workers 9,22 although in this work the tumors grew slower. In our study, however, the energy density was higher than in previous studies 9,22 as high-fat diets (20% corn oil) were fed to mice, while the other studies 9,22 used low fat diet (7% corn oil).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, unlike FS diet, the long-term administration of SP diet stimulated the growth of orthotopic MCF-7 xenografts in ovariectomized mice, which concur with the previous studies of Allred and co-workers 9,22 although in this work the tumors grew slower. In our study, however, the energy density was higher than in previous studies 9,22 as high-fat diets (20% corn oil) were fed to mice, while the other studies 9,22 used low fat diet (7% corn oil).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, however, the energy density was higher than in previous studies 9,22 as high-fat diets (20% corn oil) were fed to mice, while the other studies 9,22 used low fat diet (7% corn oil). The use of high-fat led to lower consumption of SP diet and hence phytoestrogen in our study than in the other studies, 9,22 which may in part explain the observed slower rate of tumor growth.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…19,35,36 GEN increased the proliferation of the MCF-7 cells in vitro in part through modulation of the IGF-I signalling pathway. 37 Furthermore, GEN is known to bind preferentially to ERb.…”
Section: Discussionmentioning
confidence: 92%
“…Isoflavones are also known to act independent of the ERs through their antiproliferative, antiangiogenic, antioxidative and anti-inflammatory properties (Setchell et al, 2002). In addition to isoflavones, soybeans also contain other bioactive components that may be associated with chemoprevention (for example, protease inhibitors, phenolic acids, lignans, phytosterols and saponins) (Allred et al, 2004). Furthermore, several studies have reported possible synergistic effects of these components (Omoni and Aluko, 2005;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%